Chapter 4 - Applications of nanotechnology in molecular imaging of the brain. - McAteer, M; Choudhury, R (2009)
Rapid advances in the field of nanotechnology promise revolutionary improvements in the diagnosis and therapy of neuroinflammatory disorders. An array of iron oxide nano- and microparticle agents have been developed for in vivo molecular magnetic resonance imaging (mMRI) of cerebrovascular endothelial targets, such as vascular cell adhesion molecule-1 (VCAM-1), E-selectin, and the glycoprotein receptor GP IIb/IIIa expressed on activated platelets. Molecular markers of glioma cells, such as matrix metalloproteinase-2 (MMP-2), and markers for brain tumor angiogenesis, such as alpha (v) beta (3) integrin (alpha(v)beta(3)), have also been successfully targeted using nanoparticle imaging probes. This chapter provides an overview of targeted, iron oxide nano- and microparticles that have been applied for in vivo mMRI of the brain in experimental models of multiple sclerosis (MS), brain ischemia, cerebral malaria (CM), brain cancer, and Alzheimer's disease. The potential of targeted nanoparticle agents for application in clinical imaging is also discussed, including multimodal and therapeutic approaches.